REPUTATION'S IMPACT ON AUDITOR SWITCHING THROUGH AUDIT DELAYS AND FINANCIAL DISTRESS IN THE ENERGY SECTOR - Al-farizi , Luthfi; Rahayu , Ruci Arizanda; Ramadhan , Arya Wahyu; Silvia , Nanda (Antis-Publisher, 2024)
General Background: Auditor switching, particularly in energy companies, can be influenced by various factors including audit opinions, audit delays, and financial distress, all of which are critical in ensuring the credibility of financial reporting. Specific Background: In Indonesia, the energy sector is vital for economic stability, yet few studies have explored how these factors influence auditor switching, particularly the moderating role of KAP (Kantor Akuntan Publik) reputation. Knowledge Gap: While previous research has identified some determinants of auditor switching, the moderating effect of KAP reputation on these relationships remains underexplored, especially in the context of energy companies in emerging markets. Aims: This study aims to determine the impact of company characteristics and audit characteristics on auditor switching, with KAP reputation as a moderator, within energy companies listed on the Indonesia Stock Exchange from 2018 to 2021. Results: The study found that audit opinions, audit delays, and financial distress significantly influence auditor switching. Moreover, the reputation of KAP moderates the effect of financial distress on auditor switching. Novelty: This research uniquely highlights the moderating role of KAP reputation, specifically within the energy sector, providing new insights into how external audit firm reputation interacts with company-specific risks to influence auditor-switching behavior. Implications: The findings contribute to a better understanding of the audit selection process in the energy sector and provide guidance for regulators and practitioners in improving audit quality and decision-making processes, emphasizing the importance of auditor reputation in mitigating the risks associated with financial distress.